Healthcare-associated COVID-19 in England: A national data linkage study. Issue 5 (November 2021) - Bhattacharya, Alex; Collin, Simon M; Stimson, James; Thelwall, Simon; Nsonwu, Olisaeloka; Gerver, Sarah; Robotham, Julie; Wilcox, Mark; Hopkins, Susan; Hope, Russell
Highlights: This is the first national report of healthcare-associated COVID-19 in England. Our study covered the first wave of the pandemic, from march to august 2020. 15% of SARS-CoV-2 infections in patients were hospital-onset healthcare-associated. These represent less than 1% of the estimated 3 million COVID-19 cases in this period. Summary: Objectives: Nosocomial transmission was an important aspect of SARS-CoV-1 and MERS-CoV outbreaks. Healthcare-associated SARS-CoV-2 infection has been reported in single and multi-site hospital-based studies in England, but not nationally. Methods: Admission records for all hospitals in England were linked to SARS-CoV-2 national test data for the period 01/03/2020 to 31/08/2020. Case definitions were: community-onset community-acquired, first positive test <14 days pre-admission, up to day 2 of admission; hospital-onset indeterminate healthcare-associated, first positive on day 3–7; hospital-onset probable healthcare-associated, first positive on day 8–14; hospital-onset definite healthcare-associated, first positive from day 15 of admission until discharge; community-onset possible healthcare-associated, first positive test ≤14 days post-discharge. Results: One-third (34.4%, 100, 859/293, 204) of all laboratory-confirmed COVID-19 cases were linked to a hospital record. Hospital-onset probable and definite cases represented 5.3% (15, 564/293, 204) of all laboratory-confirmed cases and 15.4% (15, 564/100, 859) of laboratory-confirmed cases among hospital patients. Community-onset community-acquired and community-onset possible healthcare-associated cases represented 86.5% (253, 582/293, 204) and 5.1% (14, 913/293, 204) of all laboratory-confirmed cases, respectively. Conclusions: Up to 1 in 6 SARS-CoV-2 infections among hospitalised patients with COVID-19 in England during the first 6 months of the pandemic could be attributed to nosocomial transmission, but these represent less than 1% of the estimated 3 million COVID-19 cases in this period.